الاستدلال اللغوي عند الأصوليين: مقاربة تداولية - يحيى رمضان (International Institute of Islamic Thought, 2013)
تسعى هذه الدراسة إلى الكشف عن بعض جوانب ثراء تراثنا اللغوي المتصل بقراءة خطاب الوحي وحداثته أيضاً، عبر مقاربته بأحدث التوجّهات التداولية.كما تطمح إلى الوقوف على بعض شرائط القدرتين: الوصفية، والتفسيرية، التي ميَّزت الخطاب الأصولي بوصفه نظرية في تحليل الخطاب وتأويله؛ وذلك باستكناه أحد المفاهيم المركزية في نظرية المناسبة التداولية pertinence))؛ أَقصِدُ مفهوم الاستدلال (inférence) وما يرتبط به من مفاهيم، مثل مفهومي: السياق، ومقصد المتكلّم. This study uses recent pertinence trends to demonstrate some aspects of richness in our linguistic legacy pertaining to the discourse of Divine Revelation and its temporality, and to reveal the descriptive and interpretive capabilities of the Usuli discourse (discourse of principles of jurisprudence) as being a theory in discourse analysis and interpretation. This purpose has been achieved through one of the central concepts of the theory of pertinence; i.e., the concept of inference and other relevant concepts such as context and intention.